Effects of AR on Cognitive Processes: An Experimental Study on Object Manipulation, Eye-Tracking, and Behavior Observation in Design Education - Ju Yeon Kim; Jin Kyung Choi (Sensors)
We investigate the impact of augmented reality (AR) on spatial reasoning and visualization skills in design education by analyzing users’ interaction behaviors with AR environments. Specifically, we examine how prior experience in spatial design influences engagement with AR tools. To this end, we compare the eye movement and operational behaviors of two groups: participants with a background in 3D space design (experimental group) and those without such experience (control group). Participants manipulated virtual objects within real-world environments at a 1:1 scale, and we analyzed interaction frequency, duration, and efficiency using frequency analysis and independent samples t-tests in SPSS 25. The results indicate that, although both groups engaged similarly with AR content, the experimental group demonstrated more precise manipulation and a deeper understanding of spatial relationships, leading to more efficient task completion. These findings suggest that AR-based learning experiences should be tailored to learners’ spatial reasoning abilities to maximize educational benefits. Consequently, educators should design adaptive AR environments that accommodate diverse skill levels to ensure optimized learning outcomes in spatial design education.